Normalizing Violence: Transitional Justice and the Gujarat Riots - Kapur, Ratna (Columbia Journal of Gender and Law, 2006)
In February and March of 2001, the Vishwa Hindu Parishad (VHP-World Hindu Council), a religious-based organization set up to mobilize “the Hindu masses,” sounded the drum roll of the Ram Mandir (Ram Temple) movement. The primary objective of the movement is to construct a temple on the very spot in Ayodhya where the mobs of the Hindu Right tore apart a sixteenth century mosque with their bare hands in December 1992. The VHP declared that the mosque stood precisely on the spot where “God” was born and determined to carry out its objective of constructing the temple in pursuit of the broader mission of the Hindu Right, the establishment of a Hindu state for a nation consisting primarily of Hindus. In preparation for the event, their foot soldiers visited the site of the now cordoned off area to pay respects and prepare for the bhumipuja (grand prayer). While some of these participants were returning from the site by train, allegedly shouting god chants, (“hail ‘ram rajya “‘–Hail to the Rule of Lord Ram) and anti-Muslim slogans (“Muslims Bharat chodo!”– Muslims leave India!), their bogey was purportedly set alight by mobs of Muslims as the train moved through Godhra station in Gujarat. The carnage that followed left fifty-eight Hindus dead. This event ignited the second catastrophic event-the slaughter of over two thousand Muslims throughout the state of Gujarat both within sight of the state’s law enforcement officers, who simply stood by as witnesses to the massacre, and, in some cases, with the active support of state officials. Dev, a Bollywood film directed by reputed filmmaker Govind Nihalani, depicts the isolation of the Indian Muslim in the post-Gujarat scenario where even secularists turned partisan, rendering the country’s law and order machinery into a force capable of the most horrifying violence. At the center of the power game are two police officers-Dev Pratap Singh, (Amitabh Bachchan) and Tejinder Khosla (Om Puri). Although the film is located in Bombay, it serves as a metaphor for what happened in the Gujarat riots in 2002. Dev, the Joint Commissioner of Police, is a proud and seasoned police officer representing the liberal subject with complete faith in the supremacy of law. Dev is the conscience of the film, and has a tough time comprehending the real politics behind the riots. He is initially simply disgusted, and refuses to see how the majoritarianism of the Hindus has turned into a process of gradual disentitlement and marginalisation of the Muslims. His “neutral” stance and fence-sitting political ideology persists throughout the film, until he is attacked by a young Muslim, Farhan (Fardeen Khan), an unemployed law graduate who holds Dev responsible for his father’s death. Farhan’s father, Ali Saheb, was accidentally shot and killed by the police during a march protesting police injustices against the Muslim community. Ali Saheb infused Farhan with ideas of patriotism, non-violence, and faith in the democratic process and rule of law, which are the very same liberal values to which Dev subscribes, but the violent death of his father leaves Farhan emotionally orphaned and disillusioned. He chooses the path of violence and joins forces with a corrupt and ambitious politician, Lati, with the intent to kill Dev.